SANEAMIENTO EPISTEMOLÓGICO DEL INSTITUTO DE ASILO Y SUS ALCANCES JURÍDICOS COMO DERECHO HUMANO: A LA LUZ DEL PRINCIPIO DE IGUALDAD Y NO DISCRIMINACIÓN Y OTROS PRINCIPIOS RECTORES DEL DERECHO INTERNACIONAL DE LOS DERECHOS HUMANOS - Moreno Buján, Marcela (2020)
This article exposes an epistemological restructuring of the juridical institute of asylum, in the light of the report requested by the Secretary of the Inter-american Court of Human Rights to the Dean´s office at the School of Law of the University of Costa Rica, in the context of the development of the Advisory Opinion OC-25/18, of May 30, 2018, required by the Republic of Ecuador.